Stages of restoration of medieval architectural monuments. Latvian experience - Spārītis, Ojārs (Landscape Architecture and Art, 2025)
The purpose of the article is to provide a focused overview of the evolution of measures taken to protect Latvia’s medieval architectural heritage as a value of material culture, from the restoration of the functionality of utilitarian architectural objects to the complex implementation of scientific methodological and technological techniques for the preservation of the original substance through conservation, restoration and partial restoration. In European society, both approaches to the preservation of architecture have always coexisted: both practical and aesthetic, with the latter partially appraising the artistic value in addition to its utilitarian function. The scope and attitude of their application have been dictated by rational considerations. It was only the academically educated European society of the Age of Enlightenment and the 19th century came to understand the importance of historical, symbolic, emotional and aesthetic values of architecture, laying the foundations for the theory and practice of architectural heritage preservation. In the experience of preservation of medieval architecture in Latvia, there have been both ups and downs of a prudent attitude, caused by either political cataclysms or a revisionist attitude. Taking care of the preservation of their cultural heritage, since the second half of the 18th century, the Baltic German community in Latvia have been trying to discover and nurture the evidence related to their immigration to the Baltics. This was done with encyclopaedic historical research and also with early archaeological and architectural research methods. A hundred years ago, the protection of Latvia’s cultural heritage developed as a science-and-research-based system, but due to insufficient resources, it did not become comprehensive. After the Second World War, cultural heritage preservation was dictated by a politicized approach and ideological motives. The re-establishment of Latvia’s independence in 1991 could provide support for a modern scientific, methodological and theoretical basis as well as appropriate technical and professional realization of the conservation and restoration. of medieval architectural monuments.